Determination antioxidant activities methanol extracts of bangun-bangun (Coleus amboinicus L.) Leaves with DPPH method - Kasta Gurning (Pascasarjana Universitas Negeri Medan, 2020)
Bangun-bangun (Coleus amboinicus Lour.) leaves is a plant that has various types of active compounds that can be utilized in various fields of health and food. The purpose of this research is to determine the components of the active compound contained in the sample when extract with methanol by maceration method and antioxidant activity test with DPPH method using a UV-Vis spectrophotometer. The value of antioxidant activity is determined by the amount of ability to inhibit 50% concentration of free radicals from DPPH. Phytochemical screening results of methanol extract active compounds contained alkaloids, tannins, flavonoids, terpenoids and steroids, as well as phenolic & polyphenols. The test activity of methanol extract of Coleus amboinicus leaves and ascorbic acid in the amount of 38.83 and 4.18 included in the very strong category as antioxidants. The extract of Coleus amboinicus leaves has lower activity compared to ascorbic acid and has the potential to be used as a natural antioxidant in preventing and minimizing the effects of free radicals. Keywords: Coleus amboinicus Lour, Antioxidant, Methanol extract, IC50, DPPH